Grand strategy - Layton, Peter (Brisbane, Australia : Peter Layton, 2018)
This book addresses the 'blank sheet of paper' problem. When given a blank sheet of paper and asked to imagine a new grand strategy or to revise or even critique an existing one where should you start? There is no other book that answers this question. There are many books and articles on the history of specific grand strategies and numerous others that advocate a particular grand strategy that a specific nation - usually America - should adopt. None however, take an approach that can be easily applied to new and emerging grand strategy problems of any country or organisation. Illustrating this, the book's case studies examine various grand strategies of a uniquely diverse range of countries and organisations to reveal why they succeeded - or not. The book is deliberately designed to allow busy people to understand and apply grand strategy to solve complex, real world problems. Drawing on recent studies in cognition, and integrating contemporary international relations theories, the book develops a lucid and structured way for us to think better about grand strategy. The case studies include: US Iraq War Grand Strategy 1991-1992, Liberation Tigers of Tamil Eeelam (LTTE) Grand Strategy 1990-2002, Soviet Union Détente Grand Strategy 1965-1980, US ERP (Marshall Plan) Grand Strategy 1947-52, Iranian Hezbollah Grand Strategy 1982-2006, British Interwar Appeasement Grand Strategy 1934-1939, British Malayan Emergency Grand Strategy 1948-1960, Landmines Ban Campaign Grand Strategy 1992-1999, US Iraq Regime Change Grand Strategy 2002-2003.
1. Present failings, new approaches -- 2. The idea of grand strategy -- 3. Making better grand strategies: theoretical foundations -- 4. Making better grand strategies: a practical approach -- 5. Denial grand strategies -- 6. Engagement grand strategies -- 7. Reform grand strategies -- 8. When to use grand strategies to solve a problem (and when not).
Includes bibliographical references (pages 244-264) and index.
Keywords: Strategic planning; Strategic culture; Strategy -- Case studies; Strategy -- History; National security -- Case studies; National security -- History; Military policy; World politics -- 1975-1985.